2006
DOI: 10.1088/0957-0233/17/7/009
|View full text |Cite
|
Sign up to set email alerts
|

New laser technology to determine present weather parameters

Abstract: Present weather sensors are becoming increasingly important as a means to augment networks of automated weather stations and extend the capability of manned observations. The classification of hydrometeors is one of the principal tasks that is addressed by present weather sensors. In this paper we discuss new laser based technology for this purpose. The system improves upon current precipitation monitors by using a derivative of Phase Doppler Anemometry techniques to accurately determine particle speed and siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 22 publications
(45 reference statements)
0
25
0
Order By: Relevance
“…Computations are carried out assuming a spherical shape and a correction accounting for oblateness is then implemented. More details can be found in Ellis et al (2006) or in the device documentation (CampbellScientific-Ltd, 2012). Actually authors found possible to improve the oblateness correction of the PWS100 rationale (Gires 5 et al, 2017a) and used it in previous studies (Gires et al, 2015).…”
mentioning
confidence: 99%
“…Computations are carried out assuming a spherical shape and a correction accounting for oblateness is then implemented. More details can be found in Ellis et al (2006) or in the device documentation (CampbellScientific-Ltd, 2012). Actually authors found possible to improve the oblateness correction of the PWS100 rationale (Gires 5 et al, 2017a) and used it in previous studies (Gires et al, 2015).…”
mentioning
confidence: 99%
“…The first ones were impact disdrometers (Joss and Waldvogel 1967), and now optical ones (Loffler-Mang and Joss 2000, Ellis et al 2006, Battaglia et al 2010, Frasson et al 2011) are more commonly used for operational and research purposes. The great advantage of these devices with regards to more conventional rain gauges is that they do not measure only a rain rate (or rainfall depth) but information about size and fall velocity for all the hydrometeors passing through the sampling area whose size is few tens of cm 2 .…”
mentioning
confidence: 99%
“…Computations are carried out assuming a spherical shape, and a correction accounting for oblateness is then implemented. More details can be found in Ellis et al (2006) or in the device documentation (Campbell-Scientific-Ltd, 2012). Actually the authors could improve the oblateness correction of the PWS100 rationale (Gires et al, 2017) and used it in previous studies (Gires et al, 2015).…”
Section: Brief Description Of the Devices' Functioningmentioning
confidence: 99%
“…Now the most commonly used operationally are optical ones. They are made of a transmitter generating one or several laser sheet(s) and receiver(s) measuring either the occluded light (Loffler-Mang and Joss, 2000;Battaglia et al, 2010;Delahaye et al, 2006;Frasson et al, 2011) or the refracted light (Ellis et al, 2006) from the drops falling through a sampling area of roughly a few tens of cm 2 . The received signal is then processed to estimate the size (more precisely an equivolumic diameter, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation